HUBUNGAN KEBIASAAN SENAM AEROBIK DENGAN KEJADIAN DISMINORE PRIMER DI SANGGAR SENAM GRAHA MULIA PROBOLINGGO: The Correlation Between Aerobik Exercise Habits and Incidence of Primary Dysminorrhea at Graha Mulia Studio in Probolinggo - Maulida Rosyita; Tutik Hidayati; Muthmainnah Zakiyyah (Forind Press, 2023)
Primary dysmenorrhea is a common menstrual disorder among women and can significantly affect their daily quality of life. This study aimed to analyze the Correlation between aerobic exercise habits and the incidence of primary dysmenorrhea among members of Graha Mulia Studio in Probolinggo. The study employed a quantitative approach with a cross-sectional design. The population consisted of all members of Graha Mulia Studio, totaling 30 individuals, and a total sampling technique was used for data collection. Informed consent and a questionnaire were utilized to collect data, which were subsequently processed using editing, scoring, coding, tabulating, and entering techniques. The data were then analyzed using the Chi-Square test. The results of the data analysis indicated a significant relationship between aerobic exercise habits and the incidence of primary dysmenorrhea among members of Graha Mulia Studio (P Value = 0.003; α = 0.05). Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, signifying that there is a significant relationship between aerobic exercise habits and the incidence of primary dysmenorrhea at the gymnastics studio. This research concludes that aerobic exercise habits hold potential as an alternative method for alleviating symptoms of primary dysmenorrhea. With this finding, aerobic exercise can be considered a beneficial relaxation option for women experiencing dysmenorrhea. Efforts to raise awareness and encourage participation in aerobic exercise can provide significant benefits in reducing dysmenorrhea symptoms among women.